2013
DOI: 10.1016/j.cca.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Gene methylation in gastric cancer

Abstract: Gastric cancer is one of the most common malignancies and remains the second leading cause of cancer-related death worldwide. Over 70% of new cases and deaths occur in developing countries. In the early years of the molecular biology revolution, cancer research mainly focuses on genetic alterations, including gastric cancer. Epigenetic mechanisms are essential for normal development and maintenance of tissue-specific gene expression patterns in mammals. Disruption of epigenetic processes can lead to altered ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
244
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(252 citation statements)
references
References 232 publications
7
244
0
1
Order By: Relevance
“…cells (37,38). It has been identified that there is an association between hypermethylation of SOCS-1 and the pathogenesis of different tumors, including chronic myeloid leukemia, human melanoma and gastric cancer (39)(40)(41) (43) failed to detect a correlation between P16 methylation and prognostic factors. P16 hypermethylation has been associated with progression of the disease, as the frequency of this phenomena increases as the disease progresses through its different stages of evolution, beginning at 0% at the preclinical phase or monoclonal gammopathy of undetermined significance, at 0% for the asymptomatic phase, and to 41.8% for symptomatic MM and 80% for plasma cell leukemia (3,4,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…cells (37,38). It has been identified that there is an association between hypermethylation of SOCS-1 and the pathogenesis of different tumors, including chronic myeloid leukemia, human melanoma and gastric cancer (39)(40)(41) (43) failed to detect a correlation between P16 methylation and prognostic factors. P16 hypermethylation has been associated with progression of the disease, as the frequency of this phenomena increases as the disease progresses through its different stages of evolution, beginning at 0% at the preclinical phase or monoclonal gammopathy of undetermined significance, at 0% for the asymptomatic phase, and to 41.8% for symptomatic MM and 80% for plasma cell leukemia (3,4,20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Homeostasis of the gastrointestinal epithelium is 87 [47,[69][70][71][72][73][74][75]232] Fzd-3 [78] CTNNB1 [9,[88][89][90][91][92][93]96,97] LRP6 [228] TCF7L2 [98][99][100] PPN [79] CDH17 [80] EZH2 [81] HMGA1, HMGA2 [210,211] YY1 [86] TC1 (C8orf4) [201,202] miR-17-92 [161] mir-10a [168] has-miR-335 [166] hsa-miR-375 [163] Downregulation or function inhibition in gastric cancer Downregulation by hypermethylation Inactivation by miRNAs APC [145,146] APC [175] sFRP1, sFRP2, sFRP4, sFRP5 [78,96,149] AXIN2 [159] WIF-1 [144,149] EZF1 [78] Dkk-1, Dkk-2, Dkk-3 [59,144,148,…”
Section: Wnt/b-catenin Pathway In Gastric Carcinogenesismentioning
confidence: 99%
“…Indeed, APC is one of the genes commonly hypermethylated in gastric cancer [145,146] . Moreover, hypermethylation of APC promoter contributing to moderate activation of Wnt signaling was associated to the development and progression of gastric adenomas, which are considered as premalignant lesions of gastric adenocarcinoma [145] .…”
Section: Loss Of Wnt Repressor Function In Gastric Cancermentioning
confidence: 99%
“…DNA methylation occurs by the addition of a methyl (CH 3 ) group to the fifth carbon of cytosine residues in CpG islands (2,6). CpG islands are located in the promoter regions of about half of all of the genes in the genome and are regions rich with guanine and cytosine.…”
Section: Dna Methylationmentioning
confidence: 99%
“…Physiologically, DNA methylation is seen in events such as X chromosome inactivation, differentiation in the stage of embryogenesis, and genomic imprinting (6). DNA methylation is catalyzed by the enzymes called DNA methyltransferase (DNMT) (6). While the continuity of DNA methylation occurs with the enzyme DNMT1, DNMT3A and DNMT3B enzymes serve in de novo DNA methylation (7).…”
Section: Dna Methylationmentioning
confidence: 99%